(untitled) (The Journal of Psychology and Sociology, 2012)
Visual sociology is at the stage of formation theoretical terminology logical, methodical base. It uses images and other spectacular objects to for analyze the society and culture. The article is an attempt to analyze the phe-nomenon of “visual sociology” in sociology today, systematic theoretical basis, the review of techniques of research.